SPICE-HL3: Single-Photon, Inertial, and Stereo Camera dataset for Exploration of High-Latitude Lunar Landscapes. - Rodríguez-Martínez, David; Van der Meer, Dave; Song, Junlin; Bear, Abhishek; Pérez-del-Pulgar-Mancebo, Carlos Jesús; Olivares-Méndez, Miguel Ángel (Springer Nature, 2026)
Exploring high-latitude lunar regions presents a challenging visual environment for robots. The low sunlight elevation angle and minimal light scattering result in a visual field dominated by a strong contrast featuring long, dynamic shadows. Reproducing these conditions on Earth requires sophisticated simulators and specialized facilities. We introduce a unique dataset recorded at the LunaLab from the SnT - University of Luxembourg, an indoor test facility designed to replicate the optical characteristics of multiple lunar latitudes. Our dataset includes images, inertial measurements, and wheel odometry data from robots navigating different trajectories under multiple illumination scenarios, simulating high-latitude lunar conditions from dawn to nighttime with and without the aid of headlights, resulting in 88 distinct sequences containing a total of 1.3 M images. Data was captured using a stereo RGB-inertial sensor, a monocular monochrome camera, and, for the first time, a novel single-photon avalanche diode (SPAD) camera. We recorded both static and dynamic image sequences, with robots navigating at slow (5 cm/s) and fast (50 cm/s) speeds. All data is calibrated, synchronized, and timestamped, providing a valuable resource for validating perception tasks from vision-based autonomous navigation to scientific imaging for future lunar missions targeting high-latitude regions or those intended for robots operating across perceptually degraded environments.
The dataset is publicly available at Zenodo: https://doi.org/10.5281/zenodo.13970078. All code described in this paper can be accessed at https://GitHub.com/spaceuma/spice-hl3.
Keywords: Robótica; Vehículos autónomos; Luna - Exploración; Sistemas de imágenes; Visual odometry; SLAM; Localization; Mapping; Lunar exploration; Single-photon imaging; Perceptually degraded; Dataset